Bestimmung charakteristischer Geometrieparameter von Thermoblech‐Wärmeübertragern. Issue 8 (4th June 2014) - Piper, Mark; Olenberg, Alexander; Tran, Julian M.; Goedecke, Robert; Scholl, Stephan; Kenig, Eugeny
<x xml:space="preserve">Abstract</x> Pillow‐plate heat exchangers are a promising alternative to conventional heat exchangers. Their design methods are based on characteristic geometric parameters, for which no established determination procedures are available in the literature. In this work, the complex pillow‐plate geometry is reproduced by accurate deformation simulations. In the following step, approximate equations describing the geometry are derived and validated. Based on this validation, suggestions for the preliminary evaluation of the characteristic geometrical parameters are made.